Symptom severity is associated with leftward lateralization upon contextual modulation of visual vertical in patients with schizophrenia - Razzak, Abdul Rima; Jahrami, Haitham; Husni, Mariwan; Ali, Maryam Ebrahim; Bagust, Jeff (Frontiers in Psychiatry, 2022)
Background: Contextual processing dysfunction in patients with schizophrenia (SCZ) is not uniform and task-dependent. In SCZ, studies on the rod and frame test (RFT), which evaluates contextual modulation of verticality perception are sparse. A main study that utilized a two-alternative forced choice design for judging rod verticality reported equivalent strength of RFT contextual modulation in healthy controls and SCZ. The current study aims to uncover any potential differences in contextual modulation between controls and SCZ with an adjustment method on a computerized RFT. Methods: 17 healthy controls and 15 SCZ aligned an oriented rod to their perceived vertical with a computer mouse under four randomized frame presentations: absent frame, non-tilted (Frame0°), or tilted by 18 degrees leftward (Frame-18°) or rightward (Frame+18°). Rod deviation error was assigned a negative or positive value when aligned leftward or rightward, respectively, of 0°. Signed and absolute errors, the rod and frame effect (RFE), and intra-individual variability (inconsistency) were used for analysis. Results: There was no group difference in rod alignment errors or derived measures, except that SCZ displayed greater inconsistency in rod alignment, compared to controls. The negative symptom scale (PANSS-N) scores correlated positively with the variability measure and with unsigned Frame-18° error. Conclusions: Only the variability measure was sensitive enough to distinguish between controls and SCZ. SCZ with more severe negative symptoms had the largest variability in rod alignment, probably reflecting a state of indifference. The larger deviation errors only with a leftward tilted frame, as PANSS-N scores increased, may indicate a lateralized attentional abnormality that is correlated with severity of symptoms in SCZ.